Investigation of the In Vivo Performance of Metal-on-Metal Motec Total Wrist Arthroplasty—An Explant Analysis - Kandemir, Göksu; Julian, Harriet S.; Joyce, Thomas J.; Brown, Daniel J. (Journal of Wrist Surgery, 2024)
Background Despite the Motec metal-on-metal (MoM) total wrist arthroplasty (TWA) being among the most implanted and most reported implants, there remains concern about the articulation following the issues in hips, where early wear led to catastrophic failure.Materials and Methods Explant analysis was undertaken on seven MoM Motec wrists, explanted for technical issues in the first 3 years postimplantation, at the macro-, micro-, and nanoscales.Results Compared with unworn Motec implants, five of the explanted heads and five of the cups became smoother in vivo. The articulating surfaces of every explanted component had negative skewness. The articulating surfaces of the components did not show any of the major damage associated with hip implants but did demonstrate multidirectional scratches and dark marks mainly situated toward their equator. Four explants showed indentation marks on the rims of their cups and necks from component impingement. The nano- and macroscale observations suggested abrasive wear to be the dominant wear mechanism. Most components demonstrated evidence of self-polishing.Conclusion In the short term, the MoM Motec TWA does not seem to be affected by the wear issues seen in failing MoM total hip replacements with all of the explanted Motec components remaining within manufacturing tolerances
Keywords: wrist replacement; wrist arthroplasty; wear; failure; indentation; metal-on-metal